2021
DOI: 10.11591/edulearn.v15i2.19271
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging student ethical behavior through ethical climate in higher education

Abstract: This study investigated the direct and indirect effects of learning styles, ethics education, and ethical climate on student’s ethical behavior. The samples were obtained through a proportionate random sampling technique so that 273 students had taken the courses of conservation education, professional ethics for teachers, and business ethics. The data were collected using questionnaires and analyzed using path analysis. The research findings showed that learning styles and ethical education could directly inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Hypothesis 1 Byerly et al (2002) found that ethics instruction sensitizes business students to ethical issues (Byerly, Dave, & Medlin, 2002). According to Susilowati et al (2021), ethical education could directly influence the ethical behaviour of students. It is supported by Kolb and Kolb (2005) that found that in-depth ethics education influences ethical behaviour.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothesis 1 Byerly et al (2002) found that ethics instruction sensitizes business students to ethical issues (Byerly, Dave, & Medlin, 2002). According to Susilowati et al (2021), ethical education could directly influence the ethical behaviour of students. It is supported by Kolb and Kolb (2005) that found that in-depth ethics education influences ethical behaviour.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…However, some students do find traditional teaching styles as their preferable style (Covill, 2011). The style of learning influences the behaviour of students in higher educational institutions (Susilowati et al, 2021). According to the Deep Learning Theory, the learning styles of the students will stimulate the deep learning process.…”
Section: Hypothesismentioning
confidence: 99%
“…There are several implications to the problem of academic dishonesty of students for business schools. The first implication regards ethical value (Susilowati et al 2021). It is crucial university degree programs inculcate students in the hope that students will internalise ethical behaviours and be better prepared for future employment (Mulisa & Ebessa, 2021).…”
Section: Implications For Business Collegesmentioning
confidence: 99%